The dynamic landscape : design, ecology and management of naturalistic urban planting - Dunnett, Nigel; Hitchmough, James (London : Taylor & Francis, 2008)
- Introduction to naturalistic planting in urban landscapes / James Hitchmough and Nigel Dunnett##- The changing nature of ecology : a history of ecological planting (1800-1980) / Jan Woudstra##- Contemporary overview of naturalistic planting design / Noel Kingsbury##- The dynamic nature of plant communities : pattern and process in designed plant communities / Nigel Dunnett##- A methodology for ecological landscape and planting design : site planning and spatial design / Darrel Morrison##- Naturalistic herbaceous vegetation for urban landscapes / James Hitchmough##- Exploring woodland design : designing with complexity and dynamics : woodland types, their dynamic architecture and establishment / Roland Gustavsson##- Wetlands and water bodies / Wolfram Kircher##- Communicating naturalistic plantings : plans and specifications / Nigel Dunnett, Wolfram Kircher, and Noel Kingsbury##- Creative management / Hein Koningen##- The social and cultural context of ecological plantings / Anna Jorgensen.
Originally published: 2004.
Includes bibliographical references and index.
boek